Monitoring Water Level and Water Quality in Rainwater Harvesting Tank using Internet of Things (IoT) Device - Rahmat, Siti Nazahiyah; Looi, Zhe Hui (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
In the content of Fourth Industrial Revolution (4IR), the Internet of Things (IoT) is encouraged to be implemented in various areas of the industry, including the hydrology industry. The water quality parameters such as pH value and turbidity of water can be monitored via the IoT device. Thus, in this study, the objectives are to monitor the water level, pH value and turbidity of water in the rainwater harvesting (RWH) storage tank built using IoT devices, and to estimate the suitable volume of RWH storage tank on the rooftop of Kumpulan Perubatan Johor (KPJ) Batu Pahat Specialist Hospital. The combination of ultrasonic sensors, pH sensors, turbidity sensors and rain gauge with the Arduino were utilized for the water monitoring system installed at the RWH storage tank at KPJ Batu Pahat Specialist Hospital. The output of the data, including water level, pH value, turbidity and rainfall depth were monitored through the online portal of MyAgriTECH Monitoring System within six months from November 2020 to April 2021. The time interval for the measurement of the parameters was every 10 minutes, from the beginning until the end. The water level obtained ranged from 132.15 cm to 184.11 cm. The pH value recorded were ranged from 5.45 to 12.38, whereas the lowest turbidity and highest turbidity was 9.25 NTU and 67.11 NTU, respectively. For the estimation of optimum size for rainwater harvesting storage tank, the results obtained was 5 m3. The use of IoT device in monitoring water level and water quality in RWH tank can be implemented due to RWH system is indeed one of the alternatives to solve the problem of water supply.